Answer:
[tex]2(4 + 7) = 22[/tex]
[tex]3(\frac{1}{3} - p) = 1 - 3 p[/tex]
Step-by-step explanation:
Given
1 & 2
Required
Rewrite and simplify
[tex]1.\ 2(4 + 7)[/tex]
Apply distributive property
[tex]2(4 + 7) = 2 * 4 + 2 * 7[/tex]
[tex]2(4 + 7) = 8 + 14[/tex]
[tex]2(4 + 7) = 22[/tex]
[tex]2.\ 3(\frac{1}{3} - p)[/tex]
Apply distributive property
[tex]3(\frac{1}{3} - p) = 3*\frac{1}{3} - 3 * p[/tex]
[tex]3(\frac{1}{3} - p) = \frac{3}{3} - 3 * p[/tex]
[tex]3(\frac{1}{3} - p) = 1 - 3 * p[/tex]
[tex]3(\frac{1}{3} - p) = 1 - 3 p[/tex]